Use of innovative technologies for improving water accounting and financial viability of water consumer associations [Abstract only] - Anarbekov, Oyture; Khodjaev, Shovkat (2019)
Agriculture is an essential sector of Uzbekistan’s economy, with 17.6% of GDP in 2016 and engaging about 26% of the labor force. Having dry climatic conditions, with annual rainfall of 100–300 mm, agriculture is an abundant consumer of the country’s natural resources. More precisely, the agricultural sector constitutes 92% of Uzbekistan’s total water use, which is on average of 56 billion cubic meters of water. This is equal to 60% of all water use in Central Asia. By 2020, irrigated area of Uzbekistan is forecast to increase between 5 and 11% and overall demand for water resources could increase up to 19%. Taking into account the growing pressure on water resources, the Government of Uzbekistan is introducing water conservation policies to mitigate existing and future stresses to water sector. However, to date neither incentives to introduce water saving technologies nor penalties on water users for violating the order of water use have been effective. A lack of incentives for water savings is a key factor affecting water use decisions. In Uzbekistan, water supply for water users, specifically for agriculture is at the expense of the state budget and considered free of charge for the users. Thus, government interventions aimed at the rational use of water resources have minimal impact. This could explain the fact that water application by farmers often exceeds, by several times, the biological requirement for agricultural crops. As part of a larger project to support water savings and water productivity improvements at the farm level in Uzbekistan, the project team is introducing Smartstick technology. Smartsticks are a low-cost, crowd-sourced technology to measure water level and corresponding discharge volume on a real-time basis. Within the project, Smartsticks are being used to estimate water consumption and whether the implementation of water tariffs influence water use decisions by farmers. Furthermore, this technology helps effective data transmission on discharge flow between farmers and Water Consumer Associations via GSM that builds corresponding trust. The technology and the broader research will be used to formulate recommendations to the Government of Uzbekistan on new water payment policies at the WCAs level as a means to support rational water use and generate revenue for water delivering organizations across regions.